Arsenic Promotes NF‐Κb‐Mediated Fibroblast Dysfunction and Matrix Remodeling to Impair Muscle Stem Cell Function. (8th January 2016) - Zhang, Changqing; Ferrari, Ricardo; Beezhold, Kevin; Stearns‐Reider, Kristen; D'Amore, Antonio; Haschak, Martin; Stolz, Donna; Robbins, Paul D.; Barchowsky, Aaron; Ambrosio, Fabrisia
Abstract: Arsenic is a global health hazard that impacts over 140 million individuals worldwide. Epidemiological studies reveal prominent muscle dysfunction and mobility declines following arsenic exposure; yet, mechanisms underlying such declines are unknown. The objective of this study was to test the novel hypothesis that arsenic drives a maladaptive fibroblast phenotype to promote pathogenic myomatrix remodeling and compromise the muscle stem (satellite) cell (MuSC) niche. Mice were exposed to environmentally relevant levels of arsenic in drinking water before receiving a local muscle injury. Arsenic‐exposed muscles displayed pathogenic matrix remodeling, defective myofiber regeneration and impaired functional recovery, relative to controls. When naïve human MuSCs were seeded onto three‐dimensional decellularized muscle constructs derived from arsenic‐exposed muscles, cells displayed an increased fibrogenic conversion and decreased myogenicity, compared with cells seeded onto control constructs. Consistent with myomatrix alterations, fibroblasts isolated from arsenic‐exposed muscle displayed sustained expression of matrix remodeling genes, the majority of which were mediated by NF‐κB. Inhibition of NF‐κB during arsenic exposure preserved normal myofiber structure and functional recovery after injury, suggesting that NF‐κB signaling serves as an important mechanism of action for the deleterious effects of arsenic on tissue healing. Taken together, the results from this study implicate myomatrix biophysical and/or biochemical characteristics as culprits in arsenic‐induced MuSC dysfunction and impaired muscle regeneration. It is anticipated that these findings may aid in the development of strategies to prevent or revert the effects of arsenic on tissue healing and, more broadly, provide insight into the influence of the native myomatrix on stem cell behavior. Stem Cells 2016;34:732–742